2019 ASCCP Risk-Based Management Consensus Guidelines: Methods for Risk Estimation, Recommended Management, and Validation. Issue 2 (April 2020) - Cheung, Li C.; Egemen, Didem; Chen, Xiaojian; Katki, Hormuzd A.; Demarco, Maria; Wiser, Amy L.; Perkins, Rebecca B.; Guido, Richard S.; Wentzensen, Nicolas; Schiffman, Mark
Abstract : Objective: To manage cervical screening abnormalities, the 2019 ASCCP management consensus guidelines will recommend clinical action on the basis of risk of cervical precancer and cancer. This article details the methods used to estimate risk, to determine the risk-based management, and to validate that the risk-based recommendations are of general use in different settings. Methods: Based on 1.5 million patients undergoing triennial cervical screening by cotesting at the Kaiser Permanente Northern California from 2003 to 2017, we estimated risk profiles for different clinical scenarios and combinations of past and current human papillomavirus and cytology test results. We validated the recommended management by comparing with the estimated risks in several external data sources. Results: Risk and management tables are presented separately by Egemen et al.1 and Demarco et al.2 Risk-based management derived from the Kaiser Permanente Northern California largely agreed with the management implied from the estimated risks of the other data sources. Conclusions: The new risk-based guidelines present management of abnormal cervical screening results. By describing the steps used to develop these guidelines, the methods presented in this article can provide a basis for future extensions of the risk-based guidelines. Abstract : Supplemental digital content is available in the text.